A lithium ion battery cathode with high stability and a preparation method thereof
Patent Information
- Application Number
- CN202611079109.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-20
- Publication Date
- 2026-10-27
AI Technical Summary
[0003]然而,高压实密度的正极片在实际应用中暴露出严重的稳定性问题:一方面,极片内部孔隙率极低,导致电解液的渗透阻力剧增,极片深层区域难以充分浸润,容易产生“浸润死区”,从而引发局部内阻剧增和析锂现象;另一方面,在电池长期充放电循环过程中,正极活性材料颗粒会发生持续的体积膨胀和收缩,产生巨大的交变应力,由于高压实极片内部缺乏缓冲空间且传统粘结剂(如PVDF)仅依靠微弱的物理范德华力与铝箔结合,极易导致正极活性材料层与集流体之间发生大面积脱落剥离,造成电池容量的断崖式衰减
[0019]与现有技术相比,本发明至少具有以下有益效果:本发明打破了传统物理粘结的局限,构建了内部化学铆钉和外部流体通道的协同防护体系。首先通过电晕处理赋予铝箔表面化学活性(-OH);其次,极片内部采用PAA与PVA在烘烤热场下原位交联,形成坚韧的三维包裹骨架。更为关键的是,PAA中过量的羧基(-COOH)会与铝箔表面的羟基发生酯化反应,形成极其牢固的共价键网络。这种分子级的化学铆固,赋予了极片极高的抗拉扯和抗剥离强度。在此基础上,涂布在表面的功能涂层在注液时溶解打通深层导液网络,而极片由于内部存在强大的化学交联骨架,完全能够承受涂层溶解带来的局部结构松动而不发生坍塌,从而有效兼顾了注液效率与极片长期循环的稳定性。
Smart Images

Figure CN122991994A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion battery cathode preparation technology, and particularly relates to a lithium-ion battery cathode with high stability and its preparation method. Background Technology
[0002] With the rapid development of new energy vehicles and large-scale energy storage systems, the market has placed extremely high demands on the energy density and cycle life of lithium-ion batteries. In order to achieve high volumetric energy density, high-density processes are commonly used in lithium-ion battery manufacturing to compress the electrode volume.
[0003] However, high-density cathodes have revealed serious stability problems in practical applications: on the one hand, the extremely low porosity inside the electrode leads to a sharp increase in electrolyte penetration resistance, making it difficult to fully wet the deep areas of the electrode and easily creating "wetting dead zones," which in turn causes a sharp increase in local internal resistance and lithium plating; on the other hand, during long-term charge-discharge cycles, the positive electrode active material particles undergo continuous volume expansion and contraction, generating huge alternating stress. Since the high-density cathode lacks buffer space and traditional binders (such as PVDF) rely only on weak physical van der Waals forces to bond with the aluminum foil, it is very easy for large-area peeling and delamination to occur between the positive electrode active material layer and the current collector, resulting in a precipitous decrease in battery capacity.
[0004] Therefore, there is an urgent need for a novel cathode preparation scheme that can both fully open up the efficient electrolyte wetting network and significantly enhance the interlayer bonding strength of the electrode at the microscopic molecular level, so as to effectively solve the contradiction between the difficulty of wetting high-voltage solid electrode and the delamination during cycles. Summary of the Invention
[0005] The purpose of this invention is to provide a method for preparing a lithium-ion battery cathode with high stability, addressing the shortcomings of existing technologies. By organically coupling the construction of a super-strong covalent bonding network inside the electrode with the construction of a mesoporous flow-conducting coating on the electrode surface, the cathode exhibits both excellent deep wetting rate and long-cycle anti-peeling stability.
[0006] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing a lithium-ion battery cathode with high stability includes the following steps: S1. The positive electrode current collector aluminum foil is subjected to corona discharge treatment to obtain a modified aluminum foil with a micro-rough surface structure and hydroxyl functional groups grafted onto it. S2. The positive electrode active material, conductive agent and cross-linking composite binder are mixed evenly to form a positive electrode slurry, which is evenly coated on at least one surface of the modified aluminum foil, and then dried and rolled in stages to obtain a substrate positive electrode sheet. The crosslinked composite adhesive is a composite adhesive with a three-dimensional network structure formed by in-situ crosslinking of polyacrylic acid and polyvinyl alcohol through an esterification condensation reaction. During the staged drying process, the polyacrylic acid and polyvinyl alcohol undergo a dehydration esterification reaction to form a crosslinked skeleton, and the excess free carboxyl groups in the crosslinked composite adhesive that do not participate in the crosslinking reaction undergo an in-situ dehydration condensation reaction with the hydroxyl functional groups on the surface of the modified aluminum foil to form a covalent bonded network. S3. On the surface of the positive active material layer of the substrate positive electrode sheet, a soluble functional coating is applied at intervals and cured to form a soluble functional coating that runs through the width direction of the positive electrode sheet, thereby obtaining the lithium-ion battery positive electrode; the soluble functional coating is used to dissolve and form a number of microfluidic guiding channels on the surface of the positive electrode sheet when the electrolyte is subsequently injected.
[0007] Preferably, the characteristic parameters of the soluble functional coating satisfy the following relationship:
[0008]
[0009] Where: W is the width of a single functional coating, in μm; H is the thickness of a single functional coating, in μm; D is the spacing between two adjacent functional coatings, in μm; d 50 θ represents the median particle size of the positive electrode active material in μm; θ is the porosity of the positive electrode active material layer after rolling, 0 < θ < 1.
[0010] Preferably, the soluble functional coating comprises the following components in weight percentages: 45% to 65% of a fast-dissolving agent, selected from at least one of succinic anion and ethylene carbonate; 25% to 45% of the polymer gel backbone is selected from at least one of polymethyl methacrylate and polyvinylidene fluoride-hexafluoropropylene; 5% to 15% of inorganic nanopropellers, selected from at least one of nano titanium dioxide and nano zirconium dioxide, with a particle size of 10 to 30 nm.
[0011] Preferably, in step S2, a silane coupling agent is further added to the positive electrode slurry, and the amount of the silane coupling agent added is 0.3% to 1.5% of the mass of the positive electrode active material; the silane coupling agent is selected from 3-aminopropyltriethoxysilane or 3-glycidyl etheroxypropyltrimethoxysilane.
[0012] Preferably, in step S3, the soluble functional coating is applied to the surface of the positive electrode active material layer in the form of straight stripes or a continuous hexagonal honeycomb grid pattern.
[0013] Preferably, along the width direction of the positive electrode sheet, the thickness H of the soluble functional coating exhibits a distribution characteristic of gradually decreasing from the central region of the positive electrode sheet to the two side edge regions.
[0014] Preferably, in step S2, the mass ratio of polyacrylic acid to polyvinyl alcohol is (3~5):1; to ensure that the polyacrylic acid retains an excess of free carboxyl groups in the system after esterification and crosslinking.
[0015] Preferably, in step S2, the staged drying sequentially includes: an initial drying and dehydration stage at a temperature of 80℃~100℃ and a normal pressure holding time of 0.5~2h; and a vacuum high-temperature crosslinking stage at a vacuum degree ≤-0.09MPa, a temperature of 130℃~160℃, and a holding time of 2~5h.
[0016] Preferably, in step S3, the curing method of the soluble functional coating is vacuum phase separation curing. The specific conditions are: vacuum treatment for 10 to 30 minutes in a closed chamber with a temperature of 30℃ to 45℃ and a vacuum degree of ≤-0.08MPa, so that the solvent in the coating liquid evaporates quickly, causing microphase separation of the polymer skeleton and the formation of a mesoporous structure inside the coating.
[0017] Preferably, in step S1, the conditions for the corona discharge treatment are: under an oxygen-containing atmosphere, the corona power is 1.5~3.0kW, and the treatment time is 10~25s; after treatment, the water contact angle of the modified aluminum foil surface is controlled between 15° and 35°.
[0018] In addition, the present invention also provides a lithium-ion battery cathode with high stability, which is prepared by the preparation method described above.
[0019] Compared with existing technologies, this invention has at least the following beneficial effects: This invention breaks through the limitations of traditional physical bonding, constructing a synergistic protection system of internal chemical anchors and external fluid channels. First, corona treatment imparts chemical activity (-OH) to the aluminum foil surface; second, PAA and PVA are cross-linked in situ under a baking thermal field within the electrode, forming a tough three-dimensional encapsulation framework. More importantly, the excess carboxyl groups (-COOH) in PAA undergo esterification with the hydroxyl groups on the aluminum foil surface, forming an extremely strong covalent bond network. This molecular-level chemical anchoring endows the electrode with extremely high tensile and peel strength. Furthermore, the functional coating applied to the surface dissolves during liquid injection, opening up the deep liquid-conducting network. Because of the strong internal chemical cross-linked framework, the electrode can fully withstand the localized structural loosening caused by coating dissolution without collapsing, thus effectively balancing injection efficiency and long-term cycling stability of the electrode. Attached Figure Description
[0020] Figure 1 This is a schematic diagram of the positive electrode structure in one embodiment of the present invention.
[0021] In the figure: 1. Modified aluminum foil; 2. Positive electrode active material layer; 3. Soluble functional coating. Detailed Implementation
[0022] The technical solution of the present invention will be clearly and completely described below with reference to specific embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0023] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.
[0024] According to a first aspect of this application, this application provides a method for preparing a lithium-ion battery cathode with high stability, comprising the following steps: S1. The positive electrode current collector aluminum foil is subjected to corona discharge treatment to obtain a modified aluminum foil with a micro-rough surface structure and hydroxyl functional groups grafted onto it. S2. The positive electrode active material, conductive agent and cross-linking composite binder are mixed evenly to form a positive electrode slurry, which is evenly coated on at least one surface of the modified aluminum foil, and then dried and rolled in stages to obtain a substrate positive electrode sheet. The crosslinked composite adhesive is a three-dimensional network structure formed by in-situ crosslinking of polyacrylic acid (PAA) and polyvinyl alcohol (PVA) through an esterification condensation reaction. During the staged drying process, the polyacrylic acid and polyvinyl alcohol undergo a dehydration esterification reaction to form a crosslinked backbone, and the excess free carboxyl groups in the crosslinked composite adhesive that do not participate in the crosslinking reaction undergo an in-situ dehydration condensation reaction with the hydroxyl functional groups on the surface of the modified aluminum foil to form a covalently bonded network. S3. On the surface of the positive active material layer of the substrate positive electrode sheet, a soluble functional coating is applied at intervals and cured to form a soluble functional coating that runs through the width direction of the positive electrode sheet, thereby obtaining the lithium-ion battery positive electrode; the soluble functional coating is used to dissolve and form a number of microfluidic guiding channels on the surface of the positive electrode sheet when the electrolyte is subsequently injected.
[0025] This invention breaks through the limitations of traditional physical bonding, constructing a synergistic protection system of internal chemical anchors and external fluid channels. First, corona treatment imparts chemical activity (-OH) to the aluminum foil surface. Second, PAA and PVA are cross-linked in situ under a baking thermal field within the electrode, forming a tough three-dimensional encapsulation framework. More importantly, the excess carboxyl groups (-COOH) in the PAA undergo esterification with the hydroxyl groups on the aluminum foil surface, forming an extremely strong covalent bond network. This molecular-level chemical anchoring endows the electrode with extremely high tensile and peel strength. Furthermore, the surface coating dissolves during liquid injection, opening up the deep liquid-conducting network. The electrode, with its strong chemically cross-linked framework, can fully withstand the localized structural loosening caused by pores without collapsing, effectively balancing injection efficiency and long-term cycling stability.
[0026] In one embodiment according to this application, the characteristic parameters of the soluble functional coating satisfy the following relationship:
[0027]
[0028] Where: W is the width of a single functional coating, in μm; H is the thickness of a single functional coating, in μm; D is the spacing between two adjacent functional coatings, in μm; d 50 θ represents the median particle size of the positive electrode active material in μm; θ is the porosity of the positive electrode active material layer after rolling, 0 < θ < 1.
[0029] The above parameter relationship can be defined as the dynamic seepage-matrix support equilibrium coefficient λ, i.e. Among them, the molecular part W 2 The coefficient of performance (H) is exponentially related to the cross-sectional area of the fluid reservoir formed after the channel dissolves, representing the capillary driving potential energy of the channel. The denominator incorporates the sparsity of the coating arrangement, the characteristic length of the active particle resistance, and the structural rigidity of the substrate. When λ < 2.0, the fluid potential energy is insufficient to overcome the permeation resistance of the electrode, and wetting improvement is ineffective. When λ > 6.5, the duty cycle of the coating etching the electrode surface is too large, excessively weakening the macroscopic mechanical support of the solid substrate, leading to electrode expansion and pulverization. Therefore, this relationship provides a precise physical boundary for the design of functional coatings.
[0030] In one embodiment according to this application, the soluble functional coating comprises the following components by weight percentage: 45% to 65% of a fast-dissolving agent, selected from at least one of succinic anionyl nitrile (SN) and ethylene carbonate (EC); 25% to 45% of the polymer gel backbone is selected from at least one of polymethyl methacrylate (PMMA) and polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP); 5% to 15% of inorganic nanopropellers, selected from at least one of nano titanium dioxide and nano zirconium dioxide, with a particle size of 10 to 30 nm.
[0031] The system employs a three-dimensional composition consisting of a fast-acting solvent, a polymer gel framework, and a rigid inorganic nanosupport. SN / EC acts as a fast solvent, rapidly responding to electrolyte flow to open channels; PMMA or PVDF-HFP does not completely disappear after liquid absorption but transforms in situ into a polymer gel (GPE) network, providing flexible adhesion; nano-titanium dioxide / zirconium dioxide acts as a rigid supporting medium, supporting the microchannel gaps and preventing them from being squeezed and closed during the expansion of charge and discharge, achieving efficient liquid conduction throughout its entire life cycle.
[0032] In one embodiment of this application, in step S2, a silane coupling agent is further added to the positive electrode slurry, wherein the amount of the silane coupling agent added is 0.3% to 1.5% of the mass of the positive electrode active material; the silane coupling agent is selected from 3-aminopropyltriethoxysilane (KH-550) or 3-glycidyl etheroxypropyltrimethoxysilane (KH-560).
[0033] In this process, silane coupling agents such as KH-550 / KH-560 are introduced into the slurry to construct a full-link bond. The reaction mechanism is as follows: the alkoxy group at one end of the coupling agent hydrolyzes in the dispersion system to form silanol (Si-OH), which then undergoes dehydration condensation with the hydroxyl groups on the surface of the inorganic positive electrode active material to form a strong "Si-O-metal" bond; the amino group (KH-550) or epoxy group (KH-560) at the other end undergoes amidation or ring-opening esterification reactions with the abundant free carboxyl groups (-COOH) on the PAA-PVA polymer chain under a high-temperature environment (130~160℃) of staged drying. This design builds a strong molecular-level covalent bridge between the active particles and the binder network, achieving deep anchoring of "current collector-binder network-active particles" and further improving the interlayer peel strength.
[0034] In one embodiment of this application, in step S3, the soluble functional coating is applied to the surface of the positive electrode active material layer in the form of straight stripes or a continuous hexagonal honeycomb grid pattern. The continuous hexagonal honeycomb grid pattern design allows the electrolyte to achieve cross-penetration in the XY two-dimensional plane on the electrode surface. Simultaneously, the hexagonal honeycomb structure is the most stable topological structure in nature, capable of isotropically and uniformly dispersing the anisotropic expansion stress of the positive electrode active particles during charging and discharging, greatly reducing the risk of stress concentration at the coating edges leading to cracks.
[0035] In one embodiment of this application, along the width direction of the positive electrode sheet, the thickness H of the soluble functional coating exhibits a gradient decreasing characteristic from the central region of the positive electrode sheet to the two side edges. Specifically, the coating thickness H gradually decreases from the center of the electrode sheet to the two side edges. During the electrolyte filling of large-scale energy storage or power battery cores, the electrolyte typically flows in from the edges, making the central region of the electrode sheet the most difficult to wet and resulting in the worst heat dissipation (dry core phenomenon). A thicker coating at the center, after dissolving, can form a larger embedded electrolyte reservoir, thereby balancing the electrolyte distribution across the entire electrode sheet surface and effectively eliminating the risk of lithium plating inside the cell due to uneven wetting.
[0036] In one embodiment of this application, in step S2, the mass ratio of polyacrylic acid to polyvinyl alcohol is (3~5):1; to ensure that the polyacrylic acid retains an excess of free carboxyl groups in the system after esterification and crosslinking. The mass ratio of PAA to PVA is limited to (3~5):1, ensuring an absolute excess of carboxyl groups from a stoichiometric perspective; if there is too much PVA, the PAA will be completely consumed, leaving no free carboxyl groups to anchor with the aluminum foil; therefore, limiting this ratio ensures the initiation of interfacial covalent bonding.
[0037] In one embodiment of this application, step S2, the staged drying sequentially includes: an initial drying and dehydration stage at a temperature of 80℃~100℃ and a holding time of 0.5~2h under normal pressure; and a vacuum high-temperature crosslinking stage at a vacuum degree ≤-0.09MPa, a temperature of 130℃~160℃, and a holding time of 2~5h.
[0038] Among them, the initial drying at atmospheric pressure (80~100℃) gently removes moisture and avoids solvent boiling that could cause bubbling and pitting on the electrode. The subsequent high-temperature crosslinking stage (130~160℃, high vacuum) is extremely critical. The high temperature provides activation energy for the esterification reaction, while according to Le Chatelier's principle, the high vacuum continuously removes the condensation water generated by the reaction, strongly breaking the thermodynamic equilibrium and driving the dehydration esterification reaction to be effectively completed, thus solidifying the chemical covalent network.
[0039] In one embodiment of this application, in step S3, the curing method of the soluble functional coating is vacuum phase separation curing. The specific conditions are: vacuum treatment for 10 to 30 minutes in a closed chamber with a temperature of 30℃~45℃ and a vacuum degree ≤-0.08MPa, so that the solvent in the coating liquid evaporates rapidly, causing microphase separation of the polymer skeleton and the formation of a mesoporous structure inside the coating.
[0040] In this process, the low-boiling-point solvent is rapidly evaporated under medium-temperature high vacuum, causing microphase separation of the polymer (such as PMMA) in the coating system and directly forming abundant nanoscale mesoporous structures within the coating. This self-porous coating exhibits an exponential increase in specific surface area and a several-fold increase in dissolution rate upon subsequent contact with the electrolyte.
[0041] In one embodiment of this application, in step S1, the conditions for the corona discharge treatment are: under an oxygen-containing atmosphere, the corona power is 1.5~3.0kW, and the treatment time is 10~25s; after treatment, the water contact angle of the modified aluminum foil surface is controlled between 15° and 35°.
[0042] According to the second aspect of this application, such as Figure 1 As shown, this application also provides a lithium-ion battery cathode with high stability, which is prepared by the preparation method described above; the cathode includes a modified aluminum foil 1, a cathode active material layer 2 disposed on at least one surface of the modified aluminum foil 1, and a soluble functional coating 3 disposed on the surface of the cathode active material layer 2.
[0043] The positive electrode prepared by the method of the present invention has both ultra-high anti-delamination strength and excellent self-wetting characteristics that traditional electrode sheets cannot possess at the same time, thus eliminating the hidden danger of high-energy cell cycle degradation from the root.
[0044] The advantages of the present invention will be further explained in detail below with reference to specific embodiments and comparative examples.
[0045] Example 1
[0046] A method for preparing a lithium-ion battery cathode with high stability includes the following steps: S1. Aluminum foil corona treatment: Under an oxygen-containing atmosphere, a 12μm thick aluminum foil was subjected to discharge treatment using a continuous corona generator with a corona power of 2.0kW and a treatment time of 15s. After treatment, abundant -OH functional groups were excited on the surface of the modified aluminum foil.
[0047] S2, Electrode coating and internal covalent crosslinking: Prepare the adhesive: Mix polyacrylic acid (PAA) and polyvinyl alcohol (PVA) in a mass ratio of 4:1 and dissolve them in deionized water.
[0048] Preparation of slurry: The positive electrode active material LiNi... 0.8 Co 0.1 Mn 0.1 O2 (median particle size d) 50 =10μm), conductive carbon black, and cross-linked composite binder are mixed at a solid content mass ratio of 96:2:2 and stirred evenly to prepare a positive electrode slurry.
[0049] Staged drying: The slurry is uniformly coated onto the modified aluminum foil. First stage: initial drying at 90℃ and normal pressure for 1 hour; Second stage: transfer to a vacuum oven at -0.095MPa and 145℃ for 3 hours. Under these conditions, the free -COOH of PAA undergoes dehydration condensation with the -OH on the aluminum foil surface, forming covalent bonds. After rolling, the active material layer thickness is 120μm, and the porosity θ=0.20.
[0050] S3. Phase separation curing of soluble functional coatings: Preparation of coating solution: Ethylene carbonate (50%), PMMA (40%), and nano TiO2 (10%, particle size 20nm) are dispersed in acetone.
[0051] Coating and curing: A micro-gravure coating is used to coat the electrode surface with parallel straight stripe patterns, and then the electrode is placed in a chamber at 40°C and a vacuum of -0.085MPa for 15 minutes.
[0052] Parameter settings: Coating width W=800μm, thickness H=5μm, spacing D=400μm.
[0053] Substitute the relational expression to verify: It falls within the range of 2.0 to 6.5.
[0054] The electrode sheets were then cut, wound, and injected with electrolyte to produce cylindrical battery cell A1.
[0055] Example 2
[0056] The basic steps are the same as in Example 1, the only difference being the adjustment of the coating parameters in S3: The coating width is set to W = 1000 μm, the thickness to H = 6 μm, and the spacing to D = 350 μm. (d) 50 =10μm, θ=0.20 remains unchanged).
[0057] Substitute the relational expression to verify: The voltage range of 2.0~6.5 is met. Cell A2 is obtained.
[0058] Example 3
[0059] Unlike Example 1, based on Example 1: In the preparation of the positive electrode slurry in S2, an additional 1.0% (by mass) of silane coupling agent KH-550 was added. During the preparation and vacuum high-temperature baking process, the ethoxy group at one end of KH-550 hydrolyzed and condensed with the hydroxyl groups on the surface of the inorganic particles of the positive electrode, while the amino group at the other end underwent a high-temperature amidation reaction with the free carboxyl groups on the PAA-PVA polymer chain, achieving full-link covalent bonding of the "current collector-binder network-active particles". The remaining preparation steps and soluble coating parameters were the same as in Example 1. Cell A3 was obtained.
[0060] Example 4
[0061] Unlike Example 3, based on Example 3: During the S3 coating process, the pattern of the soluble functional coating is changed from straight stripes to a continuous hexagonal honeycomb mesh. This stable topology can uniformly distribute stress during charging and discharging, while simultaneously forming two-dimensional cross-wetting channels. The remaining steps are the same as in Example 3. Cell A4 is thus obtained.
[0062] Example 5
[0063] Unlike Example 4, based on Example 4: Along the width of the positive electrode sheet, the thickness H of the soluble functional coating exhibits a gradient decreasing distribution from the center of the positive electrode sheet towards both edges. The coating thickness is maximum at the center line (6 μm), smoothly decreasing to 2 μm at the edges; this is to improve the dry core phenomenon that is difficult to penetrate in the center region of the cell during electrolyte injection. Cell A5 was thus fabricated.
[0064] Comparative Example 1
[0065] Untreated smooth aluminum foil and a single non-crosslinked PVDF binder are used; no functional coating is applied to the positive electrode surface. Cell B1 is produced using conventional processes.
[0066] Comparative Example 2
[0067] The substrate used was a conventional electrode sheet from Comparative Example 1, with the surface coated with the same soluble functional coating as in Example 1 (parameter λ=2.5). Cell B2 was thus obtained.
[0068] Comparative Example 3
[0069] The substrate electrode is the same as in Example 1. The coating parameters are adjusted to: W=500μm, H=3μm, D=500μm. Substituting these parameters into the formula yields... It is below the lower limit of 2.0. It is then used to make battery cell B3.
[0070] Comparative Example 4
[0071] The substrate electrode is the same as in Example 1. The coating parameters are adjusted to: W = 1200 μm, H = 8 μm, D = 250 μm. Substituting these parameters into the formula yields... This far exceeds the upper limit of 6.5. It is then used to manufacture battery cell B4.
[0072] The following performance tests were performed on the positive electrode and battery of the above embodiments and comparative examples respectively: 1. 180° peel strength of dry electrode (N / m): interlayer peel tensile test of dry electrode without liquid injection.
[0073] 2. Electrolyte wetting rate (%): The proportion of the dark-colored wetting area to the total area after vacuum injection and standing for 6 hours.
[0074] 3. Cyclic capacity retention (%): Record the capacity retention rate after 1500 cycles at 25℃ and 1C / 1C.
[0075] The test results are shown in Table 1.
[0076]
[0077] The analysis of the above test results is as follows: 1. Synergy between covalent network and flow channel: Comparison of Comparative Examples 1 and 2 with Example 1 shows that simply adding a coating (Comparative Example 2) increases the wettability, but it leads to loosening of the electrode layers, reducing the cycle life to 76.4%. Example 1, by constructing a covalent network internally, achieves a peel strength of 115 N / m, achieving a perfect balance between extremely high wettability (96.2%) and high cycle stability (93.8%).
[0078] 2. Influence of characteristic parameter λ: If the coating is too narrow and thin (Comparative Example 3, λ=0.375), the channel driving potential energy cannot overcome the high compaction resistance, and the wetting improvement fails; if the coating is over-etched (Comparative Example 4, λ=23.04), the mechanical support of the substrate is emptied, the electrode peel strength drops to 82N / m and pulverizes, and the cycle life drops to 80.5%.
[0079] 3. End-to-end anchoring of coupling agents: In Example 3, the introduction of the silane coupling agent KH-550 broke down the last chemical barrier between the active particles and the binder network. The peel strength increased to 140 N / m, the pulverization and shedding of active materials during long cycles was significantly curbed, and the cycle capacity retention rate increased to 95.2%.
[0080] 4. Honeycomb grid and thickness gradient design: Example 4 introduces a hexagonal honeycomb pattern. The two-dimensional interweaving not only increases the overall wettability area, but also effectively disperses the expansion tension (peel strength 145 N / m, cycle life 96.5%). Example 5 uses a thickness gradient decreasing design on this basis. The central liquid storage pool effectively wets the central arid area, and the overall wettability of the electrode reaches 99.8%, and the cycle life is increased to 97.2%.
[0081] In summary, the method for preparing the lithium-ion battery cathode provided by this invention has been synergistically designed from multiple dimensions such as microscopic chemical anchoring, topological stress dispersion and macroscopic fluid dynamics, which greatly improves the long-cycle stability of the battery.
[0082] It should be noted that the contents not described in detail in this specification are existing technologies known to those skilled in the art, and will not be elaborated here.
[0083] Based on the disclosure and teachings of the foregoing specification, those skilled in the art can make changes and modifications to the above embodiments. Therefore, the present invention is not limited to the specific embodiments described above, and any obvious improvements, substitutions, or modifications made by those skilled in the art based on the present invention are within the scope of protection of the present invention. Furthermore, although some specific terms are used in this specification, these terms are only for convenience of explanation and do not constitute any limitation on the present invention.
Claims
1. A method for preparing a lithium-ion battery cathode with high stability, characterized in that, Includes the following steps: S1. The positive electrode current collector aluminum foil is subjected to corona treatment to obtain a modified aluminum foil with a rough surface structure and grafted with hydroxyl functional groups. S2. The positive electrode active material, conductive agent and cross-linking composite binder are mixed evenly to form a positive electrode slurry, which is evenly coated on at least one surface of the modified aluminum foil. After staged drying and rolling, a substrate positive electrode sheet containing a positive electrode active material layer is obtained. The crosslinked composite adhesive is a composite adhesive with a three-dimensional network structure formed by in-situ crosslinking of polyacrylic acid and polyvinyl alcohol through an esterification condensation reaction. During the staged drying process, the polyacrylic acid and polyvinyl alcohol undergo a dehydration esterification reaction to form a crosslinked skeleton, and the excess free carboxyl groups in the crosslinked composite adhesive that do not participate in the crosslinking reaction undergo an in-situ dehydration condensation reaction with the hydroxyl functional groups on the surface of the modified aluminum foil to form a covalent bonded network. S3. On the surface of the positive active material layer of the substrate positive electrode sheet, a soluble functional coating that is soluble in electrolyte is applied and cured at intervals to form a coating that extends through the width direction of the positive electrode sheet, thereby obtaining the lithium-ion battery positive electrode.
2. The method for preparing a high-stability lithium-ion battery cathode according to claim 1, characterized in that, The characteristic parameters of the soluble functional coating satisfy the following relationship: ; Where: W is the width of a single functional coating, in μm; H is the thickness of a single functional coating, in μm; D is the spacing between two adjacent functional coatings, in μm; d 50 θ represents the median particle size of the positive electrode active material in μm; θ is the porosity of the positive electrode active material layer after rolling, 0 < θ < 1.
3. The method for preparing a high-stability lithium-ion battery cathode according to claim 1, characterized in that, The soluble functional coating comprises the following components by weight percentage: 45% to 65% of a fast-dissolving agent, selected from at least one of succinic anion and ethylene carbonate; 25% to 45% of the polymer gel backbone is selected from at least one of polymethyl methacrylate and polyvinylidene fluoride-hexafluoropropylene; 5% to 15% of inorganic nanopropellers, selected from at least one of nano titanium dioxide and nano zirconium dioxide, with a particle size of 10 to 30 nm.
4. The method for preparing a high-stability lithium-ion battery cathode according to claim 1, characterized in that, In step S2, a silane coupling agent is also added to the positive electrode slurry. The amount of the silane coupling agent added is 0.3% to 1.5% of the mass of the positive electrode active material. The silane coupling agent is selected from 3-aminopropyltriethoxysilane or 3-glycidyl etheroxypropyltrimethoxysilane.
5. The method for preparing a high-stability lithium-ion battery cathode according to claim 1, characterized in that, In step S3, the soluble functional coating is applied to the surface of the positive electrode active material layer in the form of straight stripes or a continuous hexagonal honeycomb grid pattern.
6. The method for preparing a high-stability lithium-ion battery cathode according to claim 1, characterized in that, Along the width direction of the positive electrode sheet, the thickness H of the soluble functional coating exhibits a distribution characteristic of gradually decreasing from the central region of the positive electrode sheet to the two side edge regions.
7. The method for preparing a high-stability lithium-ion battery cathode according to claim 1, characterized in that, In step S2, the mass ratio of polyacrylic acid to polyvinyl alcohol is (3~5):
1.
8. The method for preparing a high-stability lithium-ion battery cathode according to claim 1, characterized in that, In step S2, the staged drying process includes: an initial drying and dehydration stage with a temperature of 80℃~100℃ and a holding time of 0.5~2h under normal pressure; and a vacuum high-temperature crosslinking stage with a vacuum degree ≤-0.09MPa, a temperature of 130℃~160℃, and a holding time of 2~5h.
9. The method for preparing a high-stability lithium-ion battery cathode according to claim 1, characterized in that, In step S3, the curing method of the soluble functional coating is vacuum phase separation curing, specifically: vacuum treatment for 10 to 30 minutes in a closed chamber with a temperature of 30℃~45℃ and a vacuum degree ≤-0.08MPa.
10. A lithium-ion battery cathode with high stability, characterized in that: It is prepared by the preparation method according to any one of claims 1-9.
